2008
DOI: 10.1248/cpb.56.60
|View full text |Cite
|
Sign up to set email alerts
|

Neurite Outgrowth-Promoting Active Constituents of the Japanese Cypress (Chamaecyparis obtusa)

Abstract: There are many severe social problems associated with aging and reduced brain function worldwide and especially in Japan due to lengthning of the average life span. There is currently no definitive treatment for such diseases. In the course of our biological test-guided screening of Japanese woody plant extracts, we condacted several tests of biological activity on isolated biologically active constituents from woody plants. We reported the isolation of antibacterial constituents, 1,2) antioxidative constituen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 24 publications
0
17
0
Order By: Relevance
“…4) In our previous work, we reported the isolation of four new compounds (abiesanolide A, B, C and D) with an A-seco-17,14-friedolanostane skeleton along with a mariesane derivative from the ethyl acetate (EtOAc) soluble fraction of methanol (MeOH) extract of Abies sachalinensis leaves. 5) Some showed potent antibacterial activity against gram-positive bacteria.…”
mentioning
confidence: 99%
“…4) In our previous work, we reported the isolation of four new compounds (abiesanolide A, B, C and D) with an A-seco-17,14-friedolanostane skeleton along with a mariesane derivative from the ethyl acetate (EtOAc) soluble fraction of methanol (MeOH) extract of Abies sachalinensis leaves. 5) Some showed potent antibacterial activity against gram-positive bacteria.…”
mentioning
confidence: 99%
“…The EtOAc fraction (110 g) was chromatographied on a silica gel column with a gradient CHCl 3 -MeOH solvent system to afford ten fractions (Fr. [1][2][3][4][5][6][7][8][9][10]. Purification of some parts of the fractions was reported in our previous report.…”
Section: Methodsmentioning
confidence: 99%
“…Two antitumor compounds, paclitaxel and camptothecin, which are derived from woody plants, have been used clinically. In the course of our research isolating biologically active compounds from woody plants in Japan, we have reported several antioxidative compounds from Alnus japonica [1], antitumor-promoting active compounds from Chaenomeles sinensis [2], and active neurite outgrowth promoting compounds from Chamaecyparis obtuse [3]. One hundred methanol (MeOH) extracts of woody plants collected in the Hiroshima area were tested for antitumor activity, and some samples were selected for a study on the isolation of antitumor constituents.…”
Section: Introductionmentioning
confidence: 99%